Interaction of fertilization and soil water status determine C partitioning in a sedge wetland. (August 2019) - Kotas, Petr; Edwards, Keith; Jandová, Kateřina; Kaštovská, Eva
Abstract: Photosynthetic carbon (C) fixation and its partitioning in the plant-soil system are responsible for soil C sequestration and nutrient cycling. These microbially-mediated biogeochemical processess are impacted strongly by soil nutrient availability and soil moisture, which are being altered by global environmental change. We studied the interactive effects of fertilization (fertilized vs unfertilized) and water regime (high-water vs low-water level) on plant C fixation and rhizodeposition, and the subsequent microbial processing of plant-derived C substrates in mesocosms planted with the wetland sedge Carex acuta . We used a 13 CO2 pulse-labelling approach to track assimilates in plants, microbial phospholipid fatty acids (PLFA) and soils for 7 days. Fertilizer × water regime interactions affected the dynamics of root 13 C efflux, microbial utilization and final 13 C sequestration in the soil. Plants growing in high-water unfertilized soils rapidly exuded a greater proportion of 13 C into the rhizosphere, but the temporal increase in soil 13 C was lower than in the other treatments. In contrast, the greatest temporal increase in soil 13 C was observed in high-water fertilized systems. This occurred because fertilized plants were more productive and fixed more C, which resulted in larger root biomass with faster turnover and consequently larger amounts of 13 C immobilized in the high-water fertilized soils than high-water unfertilized soils. The composition of microbial communities processing the C rhizodeposits was dynamic during the 7 d study. Initially, the exuded 13 C was processed mainly by bacteria, while fungal PLFA became progressively more enriched after 7 d. This indicates that fungi were the main recipients of C in rhizodeposits at this time, regardless of nutrient availability or soil water regime. In summary, fertilization of the C. acuta sedge wetland stimulated above- and belowground production and selected for a smaller but more active microbial community dominated by fungi. Fertilization enhanced soil C sequestration of recently fixed photosynthates in this wet sedge grassland. Highlights: Ecosystem C partitioning is affected by fertilization and soil water status. Rhizodeposition responds to fluctuations in soil fertility and water levels. Structure of the active microbial community is related to short-term C rhizodeposits. Fungi are primary recipients of recent rhizodeposits regardless of soil water level.